Assessing Logistics Industry Efficiency and Identifying Determinants in Shijiazhuang, China – A Comprehensive Analysis - Tao-Xing ZHU; Hao SONG (Promet (Zagreb))
This study evaluated the efficiency of the logistics industry in Shijiazhuang City by using the DEA-BCC and Malmquist index models to analyse efficiency changes from 2010 to 2019 and compared them with seven logistics hub cities in the eastern region. The results indicate that Shijiazhuang’s logistics efficiency is high, with leading technology and management levels in the eastern region. Additionally, the Tobit regression model was used to explore factors affecting Shijiazhuang’s logistics efficiency, finding that economic development and locational advantages positively influence logistics efficiency, whereas industrial structure has a negative impact. Based on these findings, it is recommended that Shijiazhuang City enhance its logistics efficiency by improving logistics infrastructure, developing multimodal transport, leveraging locational advantages, elevating economic levels and openness, advancing logistics informatisation and nurturing high-quality logistics talent.